Ultrasound of Soft Tissue Masses and Fluid Collections - Wagner, Jason M; Rebik, Kristin; Spicer, Paul J (The Radiologic clinics of North America, 2019)
Soft tissue masses and fluid collections are frequently encountered in sonographic practice, either as principal indication for diagnostic examination or as an incidental finding during an examination performed for other indications. Sonography is a good first-line imaging modality for evaluation of superficial masses and fluid collections, but requires meticulous attention to technique to avoid diagnostic pitfalls. Although many superficial masses are diagnosed with ultrasound, there are several potential diagnostic challenges, including differentiating hematomas from sarcomas. This article provides an image-rich review of the sonographic features of common soft tissue masses, with emphasis on practical tips to accurately recognize important pathology.